India disasters report : towards a policy initiative - Parasuraman, S ed.; Unnikrishnan, P V ed. (New Delhi : Oxford University Press, 2000)
Complete and comprehensive profile of disasters in the Indian subcontinent.
Keywords: Emergency management -- India; Disasters -- India